Intra‐specific spatial aggregation in acidic grasslands: effects of acidification and nitrogen deposition on spatial patterns of plant communities. (13th June 2012) - Damgaard, Christian; Ejrnæs, Rasmus; Stevens, Carly J.
Abstract: Question: It is an old notion that pattern and process are linked in plant communities. Spatial pattern may, therefore, be a valuable indicator of community processes in space and time. Obviously, spatial aggregation may arise as the result of clonal propagation and short‐distance dispersal of seeds, but it is less well known how variation in the spatial aggregation links to plant community processes and to community responses to environmental stresses, such as eutrophication and acidification. We hypothesize that intra‐specific spatial aggregation may prove a useful indicator of structure and function in plant communities and, more specifically, that spatial aggregation in semi‐natural grasslands will increase with increasing eutrophication and acidification. Methods: The intra‐specific spatial aggregation at the level of the community was estimated using pin‐point data for all observed species at a site with a single parameter using the PÓlya–Eggenberger distribution. Results: Intra‐specific spatial aggregation correlates with biotic and abiotic gradients in the form of pH, vegetation height, species richness and species composition. The results support the hypothesis that eutrophication and acidification not only cause loss of species, but also lead to increasing intra‐specific aggregation of the component species. However, there was no significant effect of N deposition, which suggests that residual nutrients from former cultivation as well as sulphur deposition override the effect of N deposition on pH and productivity in Danish acidic grasslands. Conclusion: We suggest that intra‐specific spatial aggregation may be used as an indicator of structure and function in plant communities and as a possible early warning indicator of future species loss. Abstract : It is an old notion that pattern and process are linked in plant communities. Here the spatial pattern of plant community pin‐point cover data are summarized and regressed to various environmental drivers. We hypothesise that spatial aggregation in semi‐natural grasslands will increase with increasing eutrophication and acidification.